Uniqueness criterion for solution of abstract nonlocal Cauchy problem. (1993) - Byszewski Byszewski, L. L.
Abstract : The aim of the paper is to prove an uniqueness criterion for a solution of an abstract nonlocal Cauchy problem. A dissipative operator in the nonlocal problem and an arbitrary functional in the nonlocal condition are considered. The paper is a continuation of papers [1]-[3] and generalizes some results from [4].